Islamic financial planning towards sustainable eco-growth - Billah, Md. Masum; Saiti, Buerhan (Palgrave Macmillan, 2017)
Financial planning is undeniably important from an Islamic perspective; Muslims must be rich not only spiritually but also materially.This chapter discusses the importance, components, and processes of Islamic financial planning and the means of achieving the goals set out in a financial plan. Three major instruments, such as wasiyah, waqf, and hibah, are recommended as financial products used by financial institutions and professional organizations that can help Muslims meet their individual needs when it comes to managing and enhancing their financial plans.